The Optimization of Mechanical Phase-Shifting Transformer Tap Positions Based on an Open-Loop and Closed-Loop Hybrid Strategy - Jinjiao Lin; Jingyan Du; Shi Chen; Xinying Wang; Haodong Long; Chuyang Wang (Energies)
Phase-shifting transformers play a crucial role in power grid stability and efficiency. They adjust phase differences between loads, improve transmission efficiency, and balance loads during large-scale power transmission and grid integration. However, traditional mechanical phase-shifting transformers use fixed-tap designs with limited taps, preventing continuous and precise adjustments. This discrete adjustment method affects control accuracy and optimal tap position selection for proper power flow. This paper proposes a hybrid open-loop and closed-loop control strategy. This strategy maintains the phase-shifting transformer at its optimal tap position, enhancing system regulation precision and control effectiveness.